Pengaruh Independensi, Pengalaman, Kompleksitas Tugas, Tekanan Ketaatan Dan Etika Auditor Terhadap Audit Judgement (Studi Empiris Pada Kantor Inspektorat Se-Eks Karesidenan Surakarta) - Jayanti, Dwi; , Drs. Muhammad Abdul Aris, M.Si (2017)
This research aimed to analyze the influence of independency, experiences, task complexity, obedience pressure, and auditor's ethical toward audit judgement. This research was a quantitative one. Data were collected through a survey by using questionnaires. The population of this research are auditor working on the Inspektorat Se-Eks Karesidenan Surakarta. Determination of samples by using purposive sampling method. The analysis method of this research using multiple regression analysis. The results of this research indicate that independency, experiences, task complexity have an influence on the audit judgement. However, Obedience pressure and auditor's ethical do not have an influence on the audit judgement.